Efektivitas Akad Qardh Melalui Lembaga Koperasi Berbasis Syariah Di Desa - Devi Valentina Wijayanti (Business Finance Analyst Co., 2024)
Financial institutions such as Islamic Cooperatives do not necessarily expect to make profits by providing capital to their members. They also offer products designed to assist their members in establishing businesses, in the form of interest-free loans known as Qardhul Hasan. This article examines the Qardh contract in fiqh muamalah, its implementation within Islamic cooperative institutions, and the determinants of its effectiveness in village Islamic cooperatives. The aim of this article is to explore the effectiveness of the Qardh contract in facilitating entrepreneurship in rural areas. This article employs a descriptive analysis methodology, with data collection conducted through a literature review. This research gathers data from various sources including books, articles, journals, newspapers, and other secondary sources, without conducting field research. The findings of this study underscore the importance of employing the Qardh contract to facilitate access to capital for individuals. However, there are both driving and inhibiting factors in its implementation. This article aims to provide a comprehensive understanding of the Qardh contract and its use within financial institutions, particularly Islamic cooperatives. Keywords: Qardh, Cooperative, Sharia, Loan